Full-Length Genome Sequence of a Chikungunya Virus Isolate from the 2017 Autochthonous Outbreak, Lazio Region, Italy - Carletti, Fabrizio (Genome Announc, 2017)
We report here the genome sequence of a human chikungunya virus isolate from the ongoing autochthonous outbreak in central Italy. The sequence (East-Central-South African lineage, Indian Ocean sublineage), which is similar to recent sequences from Pakistan and India, shows E1 and E2 signatures of strains whose main mosquito vector is Aedes aegypti, although Aedes albopictus is the vector in Italy.